A splicing regulator, SR45, suppresses plant immunity by regulating salicylic acid pathway in Arabidopsis thaliana - Bui, Audrey; Bui, Arden; Gujral, Iesh; Fan, Serena; Long, Anthony; Hu, Anna; Chin, Christopher; Powers, Jordan; Yang, Ronghui; Gao, Min; Zhang, Chong; Lu, Hua; et al. (Frontiers in Plant Science, 2025)
Facing constant challenges from various pathogens and pests, plants have evolved different strategies to defend themselves both locally and systemically. A global change in RNA metabolism is one of the necessary steps to mount a long-lasting immunity against present and future invasions. Arabidopsis serine/arginine-rich 45 (SR45) is an evolutionarily conserved RNA-binding protein that regulates multiple steps of RNA metabolism. Our prior study suggested that SR45 acts as a negative regulator of plant immunity. To better understand the molecular mechanism for SR45’s defense role, we examined the metabolic profile in both Col-0 and sr45-1. The results showed a significant accumulation of pipecolic acid (Pip), salicylic acid (SA), and other potential defense compounds in sr45-1, indicating an increased systemic immunity. The sr45–1 mutant exhibited an elevated resistance to a wide range of biotrophic pathogen species and insensitivity to Pip, SA, and pathogen pretreatment. Between the two alternatively spliced isoforms, SR45.1 and SR45.2, SR45.1 seemed to be the culprit for the observed immune suppression. Upon examination of the transcriptome profile between Col-0 and sr45-1 under either mock or Pseudomonas syringae PmaDG3 challenge, we identified 1,125 genes as SR45-suppressed and PmaDG3-induced. Genes that function in SA biosynthesis and systemic acquired resistance were overrepresented, including those coding for WRKY, receptor-like kinases (RLKs), receptor-like proteins (RLPs), protein kinases, and TIR-NBS-LRR proteins. In addition, we identified significant alternative splicing activity in a list of genes due to either sr45–1 alone or both sr45–1 and PmaDG3 challenge. Among them, we characterized the effect of alternative splicing in two candidates, CBRLK1 and SRF1. Interestingly, alternative splicing in both exhibited a switch between RLPs and RLKs in the predicted protein products. Overexpressing their sr45–1 dominant isoform in Col-0 led to a partial increase in immunity, suggesting the involvement of both alternative splicing events in SR45-conferred immune suppression. In summary, we hypothesize that SR45 regulates a subset of immune genes at either transcriptional or co-transcriptional pre-mRNA splicing levels to confer its function in systemic immune suppression.